Method of forecasting the efficiency of investment and construction projects realization in a special economic zone at different stages of life cycle - D. Z. Iskandarov; S. M. Borozdina (Vestnik MGSU)
Introduction. The possibilities of using special economic zones (SEZ) in the aspect of increasing the volume of construction work performed and the number of erected real estate objects of various types are conditioned by the growth of SEZ establishment, which have significant expectations for solving several tasks and challenges existing in the construction industry. The problems of disproportion of production factors on the territory of the country lay down the negative consequences of incorrectly made decisions on the formation of sustainable socio-economic development of regions, which leads to differentiation in the location of infrastructure facilities and the emergence of imbalance in the labour of highly qualified personnel. The authors of the study believe that the necessary condition for solving these problems is the creation of prerequisites and conditions for the implementation of investment and construction projects (ICP) that have fundamental importance for the industry, concentrating economic entities in a single territorial space, applying SEZ for this purpose.Materials and methods. The described method of evaluation is based on application of linear and inverse proportionality coefficients, expressing the dependence of variables in the implementation of ICP in SEZ at different stages of its life cycle. The key method that used in framework of the scientific research is the construction of graphs of linear and parabolic functions illustrating changes in the amount of costs and the degree of influence of the project stages.Results. Perspectives on the creation of a tool to regulate the profitability of the project are discovered and described through linear and inverse proportionality coefficients. Identification of the intersection point of costs and influence of the project opens wide prospects for the implementation of the developed methodology in the development activities of the IСS enterprises, giving practical value to the conducted scientific work.Conclusions. The developed method of project efficiency assessment assumes separate application of calculation tools at each of its stages, which is connected with the peculiarity of using the above-mentioned coefficients. The visual presentation and ease application of the method greatly simplifies its application, which is especially necessary when carrying out an operational express assessment of the profitability of the project in the foreseeable future.